2022
DOI: 10.24875/hgmx.21000021
|View full text |Cite
|
Sign up to set email alerts
|

Experience in the management of injuries from dog bite in the plastic and reconstructive surgery service at the general hospital of Zacatecas

Abstract: Background: Dog bite wounds are a public health problem present in our environment. We find them from superficial wounds to large wounds with devitalization and significant loss of tissues, in addition to presenting complications such as infections, aesthetic and functional sequelae that require specialized surgical treatment. Objective: To describe the experience of 3 years in the management of dog bite wounds in the plastic and reconstructive surgery service at the General Hospital of Zacatecas "Luz González… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Wound management is critical in animal bites. It has been reported that with proper management (surgical grooming, edge debridement, and antibiotic prophylaxis), dog bites are less infectious and primary closure of the wound is possible [ 9 ]. This case also healed without infection with appropriate wound treatment and antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Wound management is critical in animal bites. It has been reported that with proper management (surgical grooming, edge debridement, and antibiotic prophylaxis), dog bites are less infectious and primary closure of the wound is possible [ 9 ]. This case also healed without infection with appropriate wound treatment and antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%